Vicarious Trauma Among Therapists Working with Sexual Violence, Cancer and General Practice - Kadambi, Michaela A.; Truscott, Derek (Canadian Journal of Counselling and Psychotherapy, 2007)
Vicarious trauma, traumatic stress and burnout were investigated among three separate groups of mental health professionals working primarily with three different client populations (sexual violence, cancer, general practice). Participants (N=221) completed the Traumatic Stress Institute Belief Scale Revision M (TSI), the Maslach Burnout Inventory (MBI) and the Impact of Events Scale (IES). Contrary to hypotheses, no significant differences were found between groups. The TSI and MBI were found to be highly correlated, suggesting psychometric overlap. It was concluded within this sample there was little evidence to support vicarious trauma as an occupational hazard unique to therapists working with trauma survivors.